Line‐time optimization technology for ultra‐large and high‐resolution liquid crystal displays. Issue 6 (28th June 2017) - Lee, Seung‐Hyuck; Jeon, Dong‐Hwan; Kim, Jong‐Man; Kim, Minkoo; Yu, Byung‐Chang; Lee, Seung‐Woo
Abstract: This paper proposes a line‐time optimization (LTO) technology for ultra‐large and high‐resolution liquid crystal display (LCD) televisions. Line‐time optimization enables a single‐bank data driver configuration without severe image degradation. When the proposed method is applied to an ultra‐high‐definition (UHD) LCD with a single‐bank data driver scheme, the LCD performance comparable to that of a dual‐bank data driver method can be obtained. The implementation of the proposed method helps in achieving desirable goals such as a reduction in the number of drivers and realization of a much more flexible design of UHD LCDs. Abstract : Line‐time optimization technology for ultra‐large and high‐resolution liquid crystal display (LCD) televisions is proposed. With the application of the proposed method, drivers at the bottom or top of the screen could be eliminated, which can lead to manufacturing cost reduction. Furthermore, the proposed method offers the advantages of greater freedom of placement of the control boards of displays.